Emergency Service Management for Road Traffic Accident Patients in a Specialized Public Hospital in Dhaka - Most Rowshona Begum; Margia Akter; Razia Begum; Nihar Sultana (Update Dental College, 2022)
Introduction: Road traffic accident (RTA) imposes an enormous public health burden and are a major threat to society nowadays. Emergency service has gained tremendous importance because of increasing RTA. Emergency medical service (EMS) can reduce the extent of death and disability. Method: This cross-sectional study aimed to assess the management of emergency service for RTA patients which covers both service receivers and service RTA patients as service receivers 50 doctors, nurses, and supporting staff as service providers were interviewed with a semi-structured questionnaire based on different variables related to emergency service management. Data were analyzed by SPSS software. Through an observational checklist, almost all the facilities in the emergency department were found available and functional according to Standard Operating Procedure (SOP) in spite of having a high doctor-patient and nurse-patient ratio. Result: The study revealed that out of 250 RTA patients majority 84.0% were male, the mean age was 34.8 (± 10.6 ) years, and the majority (84.0%) suffered from multiple injuries. It was also observed more than half (58.8%) of RTA patients waited to get emergency treatment for 2-5 minutes; where 38.4% waited for more than 5-10 minutes to get emergency treatment, almost three fourth (78.4%) got emergency medicines and the majority (83.6%) got the urgent investigation facilities from the hospital, almost all the emergency patients (89.2%) attended by a doctor within 5 minutes according to receivers found highly satisfied on overall emergency service management. Conclusion: Some important suggestions made by the service providers to improve the emergency service for RTA patients need to consider with proper attention by the authority. Update Dent. Coll. j: 2022; 12(1): 8-11